The Influence of Empowerment and Psychological Capital on Organizational Citizenship Behavior, Mediated by Job Satisfaction - Citra Puspita Dewi Lantasia; Alimuddin Rizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study investigates how employee empowerment and psychological capital in achieving employee satisfaction and their impact on the creation of voluntary behavior of employees, therefore the purpose of this study is to build an empirical model of organizational citizenship behavior (OCB) of employees through job satisfaction based on the model. psychology and empowerment. This type of research is explanatory or research that describes the effect of empowerment and psychological models on OCB with job satisfaction as a mediating variable. The data collection method used in general is the distribution of questionnaires to the sample used. The results showed that empowerment and psychological capital had a positive and significant effect on job satisfaction, psychological capital had no effect on organizational citizenship behavior, empowerment and job satisfaction had a positive and significant effect on organizational citizenship behavior.